A Pt / MWCNTs catalyst and its preparation method and application
By using organosilane autocatalytic reaction to synthesize Pt/MWCNTs catalysts in low-temperature fuel cell catalysts, the problems of insufficient CO tolerance of existing catalysts and uneven nanoparticle sizes are solved, and efficient dispersion and stability of the catalyst are achieved.
Patent Information
- Application Number
- CN202410124823.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-30
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-01-30
AI Technical Summary
The existing Pt/C catalysts are insufficient in low-temperature fuel cells, the nanoparticles are uneven in size and poor dispersion, which leads to prone to agglomeration during the electrocatalysis process, resulting in the intermediate toxic product CO, which leads to rapid deactivation of the catalyst.
The Pt/MWCNTs catalyst is synthesized efficiently by autocatalyzing reactions through repeated operation. By dispersing the platinum salt precursor and multi-wall carbon nanotubes in an organic solvent, and using organic silane with reducing properties, the platinum nanoparticles are uniformly deposited. On carbon nanotubes.
The prepared Pt/MWCNTs catalyst has uniform particle size, high dispersion, large electrochemical active area, improved CO tolerance, good stability and yield, and is suitable for low-temperature fuel cells.
Smart Images

Figure CN117936811B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fuel cell catalysts, and in particular relates to a Pt / MWCNTs catalyst and a preparation method and application thereof. Background Art
[0002] The electrocatalytic properties of platinum and platinum group metal nanoparticles have been studied for decades. They continue to be the focus of significant scientific interest due to their application as catalysts in low-temperature fuel cells. Low CO tolerance is one of the major issues affecting the performance of low-temperature fuel cells. Carbon monoxide is a well-known catalyst poison that adsorbs irreversibly on the platinum surface and significantly slows down the surface reactions. CO-Pt surface complexes are intermediate products of methanol electrooxidation in direct methanol fuel cells. In addition, CO is the main impurity present in hydrogen fuel input to polymer electrolyte membrane fuel cells due to hydrocarbon reforming. Many approaches have been used to improve the CO tolerance of Pt catalysts, such as alloying Pt with one or several elements, optimizing the nanoparticle size or surface modification by submonolayer deposition of a second element on the surface of Pt nanoparticles. Studies have shown that the activity of Pt for CO electrooxidation depends on the structure of the Pt nanoparticles, the dispersion of the catalyst and the nature of its support.
[0003] As an important component of fuel cells, the cost of catalysts accounts for about 40-60% of the cost of the fuel cell stack. At present, the mainstream catalyst is still Pt / C catalyst, and its preparation methods mainly include impregnation reduction method, microwave method, sol-gel method, microemulsion method, polyol method, etc. However, the catalyst Pt nanoparticles prepared by the above methods are uneven in size and poor in dispersion. They are easy to agglomerate during the electrocatalytic process and lead to the adsorption of a large amount of intermediate toxic product CO, which makes it quickly deactivated in practical applications and reduces its stability. Therefore, it is an urgent problem to develop a preparation method for Pt / C catalysts with simple process and high yield, and the prepared catalyst has small particle size, good stability, uniform dispersion and other characteristics. Summary of the invention
[0004] In view of the deficiencies in the prior art, the first object of the present invention is to provide a Pt / MWCNTs catalyst, wherein the Pt / MWCNTs catalyst is prepared by highly dispersed carbon nanotubes loaded with platinum nanoparticles.
[0005] The second object of the present invention is to provide a method for preparing the above-mentioned Pt / MWCNTs catalyst, which uses organosilane to react automatically and repeatedly to efficiently synthesize the Pt / MWCNTs catalyst. The preparation process is simple and has good stability.
[0006] The third object of the present invention is to provide an application of the above-mentioned Pt / MWCNTs catalyst, wherein the Pt / MWCNTs catalyst has the characteristics of uniform particle size and high dispersion, and has good electrochemical performance.
[0007] To achieve the above object, the present invention adopts the following technical solutions:
[0008] A method for preparing a Pt / MWCNTs catalyst, the preparation method comprising the following steps:
[0009] (1) In a glove box filled with high-purity inert gas, a platinum salt precursor is dissolved in an organic solvent, a carbon support is added, and the mixture is stirred to obtain a first mixed solution;
[0010] (2) adding organosilane to the first mixed solution obtained in step (1), stirring, and obtaining a second mixed solution; wherein the organosilane has a reducing property;
[0011] (3) The second mixed solution obtained in step (2) is filtered, washed, vacuum dried, and ground to obtain the Pt / MWCNTs catalyst.
[0012] Furthermore, in step (1), the platinum salt precursor is at least one of chloroplatinic acid, platinum dichloride, platinum tetrachloride, dinitrodiammineplatinum, potassium chloroplatinate, ammonium chloroplatinate and platinum acetylacetonate.
[0013] Furthermore, the platinum salt precursor is platinum dichloride.
[0014] Furthermore, in step (1), the carbon carrier is a multi-walled carbon nanotube (multi-walled carbon nanotubes (MWCNTs) provided by the Department of Chemical Engineering of Tsinghua University, with a diameter of 20-30 nm), which has a high specific surface area and can provide more reaction adsorption sites.
[0015] Furthermore, in step (1), the organic solvent is at least one of N,N-dimethylacetamide, heptane, benzene and tetrahydrofuran.
[0016] Furthermore, the organic solvent is N,N-dimethylacetamide.
[0017] Furthermore, in step (1), the mass volume ratio of the platinum salt precursor, the carbon carrier and the organic solvent is (4-20) mg: (13.2-23.5) mg: (50-100) mL
[0018] Furthermore, the mass volume ratio of the platinum salt precursor, the carbon carrier and the organic solvent is (8-12) mg: (13.2-23.5) mg: 60 mL
[0019] Furthermore, in step (1), the inert atmosphere is at least one of nitrogen and argon.
[0020] Furthermore, in step (1), the stirring time is 15-60 min and the temperature is 25°C.
[0021] Furthermore, in step (2), the organosilane is tert-butyldimethylsilane ( t -BuMe2SiH), triethylsilane (Et3SiH), triisopropylsilane ( i -Pr3SiH) and phenyldimethylsilane (PhMe2SiH), both of which are analytically pure.
[0022] Furthermore, the organosilane is tert-butyldimethylsilane ( t -BuMe2SiH).
[0023] Furthermore, the platinum salt precursor described in step (1) and the tert-butyldimethylsilane ( t -BuMe2SiH) has a mass volume ratio of (4-20) mg:(0.1-1.0) mL.
[0024] Furthermore, the platinum salt precursor and tert-butyldimethylsilane ( t -BuMe2SiH) has a mass volume ratio of (8-12) mg:(0.2-0.6) mL.
[0025] Furthermore, in step (2), the stirring time is 24-48 h.
[0026] Furthermore, in step (3), the washing is performed using isopropanol and deionized water respectively to remove N,N-dimethylacetamide and / or silane on the surface of the platinum.
[0027] Furthermore, in step (3), the vacuum drying temperature is 60-80°C and the time is 12-24 h.
[0028] The Pt / MWCNTs catalyst prepared by the above method has a particle size of 2-3 nm; the platinum loading in the Pt / MWCNTs catalyst is 10-40wt%, and under this loading, the Pt / MWCNTs catalyst has the best uniform dispersion and high electrochemical activity.
[0029] Application of the above Pt / MWCNTs catalyst: the Pt / MWCNTs catalyst can be used to prepare methanol fuel cells.
[0030] The present invention uses organosilane to react through autocatalysis and repeatedly run to efficiently synthesize Pt / MWCNTs catalyst. The present invention disperses carbon nanotube carrier and platinum salt precursor in an organic solvent, and then adds organosilane with reducing properties to the mixed organic solvent of carbon nanotube carrier and platinum salt precursor, so that platinum nanoparticles are uniformly deposited on the carbon nanotube carrier. The prepared catalyst particles have a particle size between 2-3nm, a high electrochemical active area and are uniformly dispersed.
[0031] Beneficial effects: (1) The present invention uses N,N-dimethylacetamide as a solvent and tert-butyldimethylsilane as a reducing agent to efficiently synthesize a Pt / MWCNTs catalyst with uniform particle size and high dispersion. The preparation process can be regarded as an autocatalytic reaction, which is repeatedly operated until all platinum is in a zero oxidation state and a stable particle size is reached. The silane coated on the platinum nanoparticles acts as a stabilizer to prevent the agglomeration of the nanoparticles.
[0032] (2) The process for preparing the Pt / MWCNTs catalyst provided by the present invention is carried out at room temperature without heating, and surface impurities can be washed away by isopropanol or water without the need for subsequent heat treatment. The preparation method has a simple process route, good preparation stability and yield, and is convenient for large-scale industrial production.
[0033] (3) The Pt / MWCNTs catalyst prepared by the present invention has good electrochemical properties and can be used to prepare methanol fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 TEM image and particle size distribution diagram of the Pt / MWCNTs catalyst prepared in Example 1. Figure 1 (a) is the TEM image of the Pt / MWCNTs catalyst prepared in Example 1. Figure 1 (b) is the particle size distribution diagram of the Pt / MWCNTs catalyst prepared in Example 1;
[0035] Figure 2 X-ray diffraction comparison diagram of the Pt / MWCNTs catalyst prepared in Example 1 and the commercial JM-Pt / C;
[0036] Figure 3 A comparison of cyclic voltammetry curves of the Pt / MWCNTs catalyst prepared in Example 1 and commercial JM-Pt / C; Figure 4 A comparison of the CO electro-oxidation of the Pt / MWCNTs catalyst prepared in Example 1 and the commercial JM-Pt / C;
[0037] Figure 5 This is a graph showing the electrical performance of a methanol fuel cell prepared using the Pt / MWCNTs catalyst prepared in Example 1 and commercial JM-Pt / C. Figure 5 (a) is a diagram showing the electrical performance of a methanol fuel cell prepared using the Pt / MWCNTs catalyst prepared in Example 1. Figure 5 (b) Graph showing the electrical performance of a methanol fuel cell prepared using commercial JM-Pt / C. DETAILED DESCRIPTION
[0038] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example
[0039] (1) In a glove box filled with high-purity argon, 8.0 mg of platinum dichloride (PtCl2) was dissolved in 60 mL of dimethylacetamide (DMA), and stirred for 15 min until chloroplatinic acid was completely dissolved. Then, 23.5 mg of multi-walled carbon nanotubes with a platinum loading of 20 wt% were added, and stirring was continued for 1 h until it was completely dispersed to obtain the first mixed solution;
[0040] (2) Add 0.20 mL of analytically pure t-BuMe2SiH2 into the first mixed solution obtained in step (1) and continue stirring for 24 h to obtain a second mixed solution;
[0041] (3) The second mixed solution obtained in step (2) was directly separated and washed, and was carefully washed with isopropanol and deionized water in turn. The catalyst was then placed in a vacuum drying oven to remove moisture. The temperature of the vacuum drying oven was 70°C and the drying time was 12 h. Finally, a Pt / MWCNTs catalyst with a platinum loading of 20 wt% was obtained by grinding.
[0042] Figure 1 TEM image and particle size distribution diagram of the Pt / MWCNTs catalyst prepared in Example 1. Figure 1 (a) is a TEM image of the Pt / MWCNTs catalyst prepared in Example 1. The results show that the catalyst synthesized in the present invention has a small particle size and is evenly distributed on the surface of the multi-walled carbon nanotubes without obvious agglomeration.
[0043] Figure 1 (b) is a particle size distribution diagram of the Pt / MWCNTs catalyst prepared in Example 1. The results show that the particle size of the platinum catalyst of the present invention is mainly concentrated in 2-3 nm, at which point it has the highest reaction activity.
[0044] Figure 2The X-ray diffraction (XRD) comparison diagram of the Pt / MWCNTs catalyst prepared in Example 1 and the commercial JM-Pt / C (JM 20%wt) (Shanghai Hesen Co., Ltd.) shows that the Pt / MWCNTs catalyst prepared in the present invention has a broad peak at 25°, which is related to the (002) crystal plane of the hexagonal graphite structure of the multi-walled carbon nanotubes. The representative diffraction peaks at 39.8°, 46.3° and 67.6° are attributed to the (111), (200) and (220) planes of face-centered cubic (FCC) Pt (PDF # 04-0802), which confirms the formation of Pt nanoparticles. The peak positions of the Pt / MWCNTs catalyst prepared in the present invention and the commercial catalyst are basically coincident.
[0045] At the same time, the larger the peak area and the half-peak width, the smaller the particle size. According to the full half-peak width of the Pt (220) peak, the average diameter of the Pt nanoparticles was estimated using the Debye-Scherrer equation. The average particle size of the catalyst prepared in the present invention is 2.5 nm, which is smaller than 3.6 nm of the commercial catalyst, which is consistent with the above TEM data. The Debye-Scherrer equation is shown in formula (1).
[0046] D = Kλ / β cos θ (1)
[0047] in, D is the average crystal size in nanometers, K is the shape factor (0.89 in this embodiment), λ is the X-ray wavelength, and λ CuKα = 0.15406 nm, β For Figure 2 θ The full width at halfway point of the peak.
[0048] Figure 3The cyclic voltammetry curve comparison diagram of the Pt / MWCNTs catalyst prepared in Example 1 and the commercial JM-Pt / C is as follows: prepare the working electrode, place the polishing powder (Al2O3) with a particle size of 0.5 μm and 0.05 μm on the suede surface respectively, and then polish the glassy carbon electrode (GCE) (d=3 mm) on the suede surface in sequence. Then, ultrasonically clean it in distilled water for about 5 minutes until the glassy carbon electrode is cleaned and placed in the air to dry naturally. At the same time, weigh 1 mg of Pt / MWCNTs catalyst or commercial JM-Pt / C, dissolve it in 50 μL Nafion solution (0.05 wt.%, DuPont, USA), and then ultrasonically disperse it until it is finally dispersed into a uniform suspension. Then, use a pipette to take out 5 μL of the ultrasonic suspension and apply it to the dried glassy carbon electrode surface, wait for natural drying, and set aside. All electrochemical performance tests were carried out in a traditional three-electrode system, in which a saturated calomel electrode (SCE) was selected as the reference electrode, a platinum electrode (1.0 cm×1.0 cm, 213 type) was used as the counter electrode, and a glassy carbon electrode loaded with a catalyst was used as the working electrode. All potentials were relative to SCE. The test instrument used in the experiment was the Shanghai Chenhua electrochemical workstation (CHI660D type), and the electrolyte solution used was 1 mol / L HClO4+1 mol / L CH3OH solution. The CV curve potential range was -0.2 V—1.0 V, the scan rate was 50 mV / s, and the temperature was controlled at 298 K using a constant temperature water bath throughout the experiment. The results show that in the cyclic voltammetry curve, for metal Pt tested in an acidic aqueous solution, the electrochemically active area (electrochemicalactive surface area, referred to as ECSA ) is larger, the higher the electrocatalytic activity is. ECSA It can be calculated by the adsorption and desorption of hydrogen on its surface. According to the theory of single-molecule electrochemical adsorption of hydrogen on the Pt surface, the hydrogen atom is 1 cm 2 The theoretical charge adsorbed on a Pt electrode of this area is 210 mC. Therefore, by measuring the hydrogen adsorption charge and substituting it into equation (2), the electrochemical surface area of the Pt particles can be obtained. ECSA .
[0049] (2)
[0050] A larger area represents a higher electrochemically active area ECSA This means that the Pt / MWCNTs catalyst in Example 1 has higher reaction activity.
[0051] Figure 4This is a comparison chart of CO electrooxidation between the Pt / MWCNTs catalyst prepared in Example 1 and the commercial JM-Pt / C. The specific test steps are: first, N2 is introduced into the electrolyte solution (1 M HClO4) for 20 min to eliminate O2 in the solution; then CO is introduced at a potential of 0.1 V for 15 min to saturate the electrode surface with CO adsorption; maintain this potential and introduce N2 to remove CO in the solution; finally, CV scan is performed in the potential window of -0.2 V to 1 V, and the potential scan rate is 10 mV / s. The results show that compared with the commercial JM-Pt / C, the peak potential and starting potential of CO oxidation of the Pt / MWCNTs catalyst in Example 1 are both lower, indicating that CO adsorbed on the surface of the catalyst is more easily oxidized. Example
[0052] (1) In a glove box filled with high-purity argon, 10.0 mg of platinum dichloride (PtCl2) was dissolved in 60 mL of dimethylacetamide (DMA), and stirred for 15 min until chloroplatinic acid was completely dissolved. Then, 17.1 mg of multi-walled carbon nanotubes was added, with a platinum loading of 30 wt%, and stirring was continued for 1 h until it was completely dispersed to obtain a first mixed solution;
[0053] (2) Add 0.40 mL of analytically pure t-BuMe2SiH to the first mixed solution obtained in step (1), and continue stirring for 24 h to obtain a second mixed solution;
[0054] (3) The second mixed solution obtained in step (2) was directly separated and washed, and was carefully washed with isopropanol and deionized water in turn. The catalyst was then placed in a vacuum drying oven to remove moisture. The temperature of the vacuum drying oven was 70°C and the drying time was 12 h. Finally, a Pt / MWCNTs catalyst with a platinum loading of 30 wt% was obtained by grinding. Example
[0055] (1) In a glove box filled with high-purity argon, 12.0 mg of platinum dichloride (PtCl2) was dissolved in 60 mL of dimethylacetamide (DMA), and stirred for 15 min until chloroplatinic acid was completely dissolved. Then, 13.2 mg of multi-walled carbon nanotubes was added, with a platinum loading of 40 wt%, and stirring was continued for 1 h until it was completely dispersed to obtain a first mixed solution;
[0056] (2) Add 0.60 mL of analytically pure t-BuMe2SiH2 into the first mixed solution obtained in step (1) and continue stirring for 24 h to obtain a second mixed solution;
[0057] The second mixed solution obtained in step (2) was directly separated and washed, and was carefully washed with isopropanol and deionized water in turn. The catalyst was then placed in a vacuum drying oven to remove moisture. The temperature of the vacuum drying oven was 70°C and the drying time was 12 h. Finally, a Pt / MWCNTs catalyst with a platinum loading of 40 wt% was obtained by grinding. Example
[0058] The existing commercial catalyst uses the most authoritative commercial catalyst Pt / C (20%wt JM) (Shanghai Hesen Co., Ltd.).
[0059] The catalyst prepared in Example 1 and the existing commercial catalyst Pt / C (wt20% JM) were used as the anode of the direct methanol fuel cell, the existing commercial catalyst Pt / C (wt20% JM) was used as the cathode, and the Nafion membrane 115 was used as the electrolyte membrane to prepare a membrane electrode system and assembled into a single cell for battery performance testing, wherein the anode feed was 2 M methanol solution 4mL / min, the cathode feed was oxygen 0.25 L / min, and the back pressure was not higher than 2 atm. The battery temperatures were set to 30°C, 60°C and 80°C, respectively, and the test results were obtained. Figure 5 , where (a) and (b) respectively use the catalyst prepared in Example 1 and the existing JM Pt / C catalyst as the anode material, where the Pt loading of the catalyst prepared in Example 1 and the existing catalyst is 1 mg / cm 2 Nafion was used as binder with a content of 23 wt%; the cathode was an existing commercial Pt / C catalyst with a Pt loading of 2 mg / cm 2 The binder Nafion content is 15 wt%; the electrolyte membrane is Nafion 115 membrane, and the pressure is 100 kg / cm2 at 140 °C using a hydraulic press. 2 The membrane electrode was prepared by hot pressing for 4 minutes, the cathode oxygen flow rate was 0.25 L / min, the anode methanol concentration was 2 M, the flow rate was 4 mL / min, and the methanol fuel cell release electrical performance test was carried out at 30℃, 60℃, and 80℃ respectively; Figure 5 It can be seen that the catalyst of Example 1 exhibits higher battery discharge performance than the existing commercial catalyst Pt / C (wt 20% JM).
[0060] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0061] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing a Pt / MWCNTs catalyst, characterized in that: The preparation method adopts the following steps: (1) Under an inert atmosphere, dissolving a platinum salt precursor in an organic solvent, adding multi-walled carbon nanotubes, and stirring to obtain a first mixed solution; (2) adding tert-butyldimethylsilane to the first mixed solution obtained in step (1), stirring, to obtain a second mixed solution; (3) filtering, washing, vacuum drying, and grinding the second mixed solution obtained in step (2) to obtain the Pt / MWCNTs catalyst, wherein the platinum loading in the Pt / MWCNTs catalyst is 10-40wt%; In step (1), the platinum salt precursor is platinum dichloride, and in step (1), the organic solvent is N,N-dimethylacetamide; The mass volume ratio of the platinum salt precursor described in step (1) and the tert-butyldimethylsilane described in step (2) is (4-20) mg: (0.1-1.0) mL.
2. The preparation method according to claim 1, characterized in that: In step (1), the mass volume ratio of the platinum salt precursor, the carbon carrier and the organic solvent is (4-20) mg: (13.2-23.5) mg: (50-100) mL.
3. The preparation method according to claim 1, characterized in that: In step (1), the inert atmosphere is at least one of nitrogen and argon; The stirring time is 15-60 min, and the temperature is 25°C.
4. The preparation method according to claim 1, characterized in that: In step (2), the stirring time is 24-48 hours.
5. The preparation method according to claim 1, characterized in that: In step (3), the washing is performed using isopropanol and deionized water respectively; The vacuum drying temperature is 60-80°C and the time is 12-24 h.
6. The Pt / MWCNTs catalyst prepared by the method according to any one of claims 1 to 5, characterized in that: The particle size of the Pt / MWCNTs catalyst is 2-3 nm.
7. The use of the Pt / MWCNTs catalyst according to claim 6, characterized in that: The Pt / MWCNTs catalyst is used for preparing a methanol fuel cell.
Citation Information
Patent Citations
High-platinum base-loaded carbon nano tube nanocatalyst and preparation method thereof
CN105655607A
Preparation method of nano-palladium catalyst with controllable morphology and size
CN113426442A